Remark
I didn't know this was a calculus question. How dumb of me.
f(x + h) - f(x)
==========
x + h - h
50/6 - 51/6 =( -1/6+ h)/h
The h's will disappear when the limit is taken.
answer - 1/6 which is A. If anyone else answers take their answer.
Answer:
What diagram?
Step-by-step explanation:
Answer:
Divide both sides by 9.
Step-by-step explanation:
To find the second step of the equation, we actually have to solve parts of the equation until we get to step 2.
Step 1: Add 23 to both sides.
Step 2: Divide both sides by 9.
Therefore, the second step is divide both sides by 9.
Have a lovely rest of your day/night, and good luck with your assignments! ♡
Answer:
n=0
Step-by-step explanation:
Rearrange
10+2=8−2+10
2+10=8−2+10
Combine like terms
2n+10=<u>8n−2n</u>+10
2+10=<u>6</u>+10
Subtract from both sides
2+10=6+10
2+10<u>−10=</u>6+10<u>−10</u>
Simplify
2n=6n
Subtract both sides from 6n of the equation
2=6
2<u>−6</u>=6<u>−6</u>
Solution
n=0